The husbands - Baker, Chandler (New York, NY : Flatiron Books, 2021)
"Nora Spangler is a successful attorney but when it comes to domestic life, she packs the lunches, schedules the doctor appointments, knows where the extra paper towel rolls are, and designs and orders the holiday cards. Her husband works hard, too ... but why does it seem like she is always working so much harder? When the Spanglers go house hunting in Dynasty Ranch, an exclusive suburban neighborhood, Nora meets a group of high-powered women-a tech CEO, a neurosurgeon, an award-winning therapist, a bestselling author-with enviably supportive husbands. When she agrees to help with a resident's wrongful death case, she is pulled into the lives of the women there. She finds the air is different in Dynasty Ranch. The women aren't hanging on by a thread. But as the case unravels, Nora uncovers a plot that may explain the secret to having-it-all. One that's worth killing for."--
Keywords: Women lawyers -- Fiction; Wives -- Fiction; Suburban life -- Fiction; Domestic fiction; Thrillers (Fiction)